Interview Dr. William Giannobile Editor-in-Chief Journal of Dental Research - Guerrero Acevedo, Maria Eugenia (2019)
For the Dr. William Giannobile, an internationally-recognized expert in the field of dental tissue engineering, serving as JDR Editor-in-Chief has been an amazing opportunity and one of the most rewarding endeavors in his professional career. He feel privileged to have been able to follow such capable and forward-thinking editors who have made the JDR the leading source of research findings for over a century. Under Dr. Giannobile’s leadership, the JDR has strived to match the quality of the best research journals in medicine and life sciences by publishing the results of different investigations, but also stimulating the spirit of research; promoting the development of original research in Stomatology.